2017
DOI: 10.3390/molecules22030335
|View full text |Cite
|
Sign up to set email alerts
|

Essential Oil of Aristolochia trilobata: Synthesis, Routes of Exposure, Acute Toxicity, Binary Mixtures and Behavioral Effects on Leaf-Cutting Ants

Abstract: Plants of the genus Aristolochia have been frequently reported as important medicinal plants. Despite their high bioactive potential, to date, there are no reports of their effects on leaf-cutting ants. Therefore, the present study aimed to evaluate the insecticidal activity of the essential oil of Aristolochia trilobata and its major components on Atta sexdens and Acromyrmex balzani, two species of leaf-cutting ants. The bioassays were performed regarding routes of exposure, acute toxicity, binary mixtures of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
15
0
3

Year Published

2017
2017
2021
2021

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 33 publications
(19 citation statements)
references
References 34 publications
1
15
0
3
Order By: Relevance
“…Chemical standards of these compounds were purchased from Sigma‐Aldrich® (Steinheim, Germany), except for sulcatyl acetate, which was synthetized by chemical reduction of 6‐methyl‐5‐hepten‐2‐one (sulcatone, 500 mg, 3.97 mmol; Sigma‐Aldrich®) (Fig. B) …”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Chemical standards of these compounds were purchased from Sigma‐Aldrich® (Steinheim, Germany), except for sulcatyl acetate, which was synthetized by chemical reduction of 6‐methyl‐5‐hepten‐2‐one (sulcatone, 500 mg, 3.97 mmol; Sigma‐Aldrich®) (Fig. B) …”
Section: Methodsmentioning
confidence: 99%
“…In fact, some studies have shown that populations of A. aegypti , including resistant populations, can be controlled by these products . Among the effective bioinsecticides, the EO from Aristolochia trilobata (Aristolochiaceae) stands out for its lethal and/or sublethal effects investigated in fungi, bacteria and pest insects . The compounds present in the EO of this plant species have synergistic and rapid actions on the cutter ants Atta sexdens and Acromyrmex balzani , as well as sublethal effects on the locomotion behavior of these insects .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In experiments of toxicity via contact and fumigation with the essential oil of Aristolochia trilobata to Acromyrmex balzani ants, fumigation presented LC 50 of 9.33 μL/L. Conversely, the essential oil presented low toxicity via contact [ 35 ]. In Pogostemon cablin , the concentration required to cause 50% of the mortality of ants of the species Atta sexdens rubropilosa by fumigation was of 1.30 μL L −1 [ 36 ].…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, an evaluation of its insecticidal activity demonstrated that this oil is an excellent alternative for use in controlling Aedes aegypti L. larvae and adults (Silva et al 2018). Recently, Oliveira et al (2017) found that both the oil and its main component exhibited fast, efficient activity against Atta sexdens L. and Acromyrmex balzani Emery through fumigation. To the best of our knowledge, however, no previous study has evaluated the acaricidal properties of A. trilobata oil and its major components against the phytophagous mite T. urticae.…”
Section: Introductionmentioning
confidence: 99%